2018
DOI: 10.1155/2018/2785971
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mast Cells and Type 2 Innate Lymphoid (ILC2) Cells in Lung Transplantation

Abstract: The multifunctional role of mast cells (MCs) in the immune system is complex and has not fully been explored. MCs reside in tissues and mucous membranes such as the lung, digestive tract, and skin which are strategically located at interfaces with the external environment. These cells, therefore, will encounter external stimuli and pathogens. MCs modulate both the innate and the adaptive immune response in inflammatory disorders including transplantation. MCs can have pro- and anti-inflammatory functions, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 125 publications
0
18
0
Order By: Relevance
“…ILC2 also contributes to the functions of mast cells [41,42]. Recent reports demonstrated that Il-10-secreting pulmonary ILC2 10 expresses GATA3 and produces Il-5 and Il-13 [14].…”
Section: Discussionmentioning
confidence: 99%
“…ILC2 also contributes to the functions of mast cells [41,42]. Recent reports demonstrated that Il-10-secreting pulmonary ILC2 10 expresses GATA3 and produces Il-5 and Il-13 [14].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, ILC2s present in the skin can control mast cell (MC) activity by direct interaction (97). Conversely, MC are an important source of IL-33 in vivo , contributing to ILC2 activation and type 2 immune response in disease models of multiple sclerosis (85), and helminth infection (98), a MC-ILC2 crosstalk also occurs in the lung (99). It is not yet fully understood how cutaneous antigen exposure could activate ILC2s but it is conceivable that dysregulation between MC and ILC2s could exacerbate the immune response during allergic airway inflammation and anaphylactic reaction.…”
Section: Biomarkers and Assessment Of Severity Of Allergic Respiratormentioning
confidence: 99%
“…33 Mast cells act as antigen-presenting cells, express several co-stimulatory molecules and produce wide varieties of both anti-inflammatory and proinflammatory molecules. 34,35 Mast cell degranulation breaks the peripheral tolerance in skin and cardiac allograft. 36 Mast cells are also known to produce several molecules such as histamine, fibroblast growth factor-2 (FGF-2), TGF-α, chymase and cathepsin G. These molecules contribute to the histological changes in the graft and fibrosis.…”
Section: Mast Cellsmentioning
confidence: 99%